Triple Diffusive Unsteady Flow of Eyring–Powell Nanofluid Over a Periodically Accelerated Surface With Variable Thermal Features - Khan, Sami Ullah; Vaidya, Hanumesh; Chammam, Wathek; Musmar, Sa'ed A.; Prasad, K. V.; Tlili, Iskander (Frontiers in Physics, 2020)
This research communicates the triple diffusion perspective of Eyring-Powell nano-materials configured by a periodically moving configuration. The thermal consequences of variable natures are utilized as a novelty. Combined magnetic and porous medium effects are also involved, which result in a magneto-porosity parameter. The thermophoretic and Brownian motion aspects are reported by using Buongiorno’s nanofluid theory. The formulated flow equations in non-dimensional forms are tackled with the implementation of a homotopy analysis algorithm. A detailed physical investigation against derived parameters is presented graphically. Due to periodically accelerated surface, the oscillations in velocity and wall shear stress has been examined.